Influence of Parental Monitoring, Sensation Seeking, Expected Social Benefits, and Refusal Efficacy on Tobacco and Alcohol Use in Chinese Adolescents. Issue 11 (March 2016) - Yu, Jincong; Wu, Qingfeng; Yang, Chengwu; Vrana, Kent E.; Zhou, Li; Yang, Longyu; Zhang, Hui; Yan, Dong; Li, Jiang; Teng, Shiwei; Gong, Jie; Yan, Yaqiong; et al.
Abstract : Abstract: The relationships between parental monitoring (PM), sensation seeking (SS), expected social benefits (ESB), refusal efficacy (RE), and tobacco and alcohol use (TAU) have been well documented among adolescents. However, the mechanisms by which these 4 determinants affect TAU remain unclear. Based on the Theory of Triadic Influence, this study aimed to explore how PM, SS, ESB, and RE simultaneously influenced TAU in Chinese adolescents. From September 2013 to June 2014, we used multistage cluster sampling to select 6269 students from 179 classes of 7 vocational high schools in 3 cities of China. Each student completed a battery of 5 measures: PM, SS, ESB, RE, and TAU. Then, we used structural equation modeling techniques and mediation analyses to investigate the relationships among these 5 measures, with TAU as the final dependent variable. Results demonstrated that the relationship between PM and TAU was fully mediated by ESB and RE (b = −0.18, P  < 0.001), that SS influenced TAU directly (b = 0.10, P  < 0.001) and indirectly through ESB and RE (b = 0.15, P  < 0.001), and that ESB influenced TAU directly (b = 0.09, P  < 0.001) and indirectly through RE (b = 0.28, P  < 0.001). These findings indicate that the link between PM and SS to TAU among Chinese adolescents can be explained by ESB and RE. These 4 precursory determinants can play an important role in TAU prevention among adolescents in China. Abstract : Supplemental Digital Content is available in the text